Ergonomic workload and well-being of nurses working in shifts - Kulczycka, Kinga Dorota; Szczuchniak, Bożena; Stychno, Ewa; Kosicka, Bogumiła (Journal of Education, Health and Sport, 2017)
Admission. Operating time is determinant of a healthy lifestyle. Shift work carries with it many negative health effects. Difficulties in adjusting to changing biological clock functioning day and night are the cause of stress and lack of tolerance by the body. Biological effects associated with the disorder are biological rhythms that contribute to sleep disorders. The aim of the study was to investigate health problems of nurses working in shifts resulting from nieergonomicznego workload. Findings. Nurses report the occurrence of many symptoms of discomfort associated with shift work, which are not due to report after medical advice. The workload is greater in the group performing professional activities in non-standard times. Being is worse in the group of nurses working in shifts. Conclusions Among the most common health problems, up to 63.5% of nurses declares chronic fatigue, 40.6% of cardiovascular problems, and 28.1% gastrointestinal disorders. Employees working in two shifts often have trouble sleeping, consisting of waking several times during the night, than who work in shift system. Physical activity and spending time with your family or loved ones reduces the frequency of problems. The vast majority (65.7%) of respondents among shift workers, occupational exposure has been associated with an accident or work.